Proteinuria in children with autosomal dominant polycystic kidney disease - Seeman, Tomáš; Pohl, Michael; John, Ulrike (Minerva pediatrica, 2018)
BACKGROUND: Proteinuria is a common complication in adults with autosomal dominant polycystic kidney disease (ADPKD) and serves as a risk factor for progression. However, proteinuria has rarely been examined in children with ADPKD and the type of proteinuria has not yet been investigated. The aim of the study was to assess the prevalence and to analyse the types of proteinuria in children with ADPKD. METHODS: Children with ADPKD followed-up in our tertiary centres during the years 2012-2013 were investigated in a cross-sectional study. Morning urine was tested for total protein (PROT), albumin (ALB) and alpha-1-microglobulin (AMG). Renal function was assessed from serum creatinine as estimated glomerular filtration rate. RESULTS: Thirty-seven children of median age 11.2 (2.0-18.0) years were investigated. Median (range) PROT, ALB and AMG (in mg/mmol creatinine) were 15.1 (6.2-64.8), 2.54 (0.54-37.25) and 3.22 (0.04-10.16), respectively. Pathological total proteinuria (>22) was found in 30% of children, albuminuria (>2.2) in 49% of children and alpha-1-microglobulinuria (>0.55) in 65% of children. No correlation was found between PROT, ALB or AMG and office blood pressure, kidney size or estimated glomerular filtration rate. CONCLUSIONS: Proteinuria in children with ADPKD is a frequent finding, the most common type is tubular proteinuria. It should be measured in all ADPKD children.
Keywords: hodnoty glomerulární filtrace; Cross-Sectional Studies; Prevalence; albuminurie; polycystické ledviny autozomálně dominantní; Disease Progression; krevní tlak; progrese nemoci; mladiství; kreatinin; proteinurie; mužské pohlaví; prevalence; Proteinuria; průřezové studie; dítě; Child; Alpha-Globulins; Child, Preschool; ženské pohlaví; Blood Pressure; Humans; předškolní dítě; alfa-globuliny; Polycystic Kidney, Autosomal Dominant; rizikové faktory; Creatinine; Albuminuria; Female; Risk Factors; Adolescent; lidé; Male; Glomerular Filtration Rate